Investigation of Chemokine and Microbiome Profiles in Gingival Health and Disease in Humans - Bamashmous, Shatha (My University, 2019)
Periodontal health is maintained by various host immune mechanisms. Neutrophils are a crucial component of health representing the first line of defense against microbial challenge. The migration and activation of these key effector cells in the gingiva are orchestrated by complex networks of host mediators called chemokines and cytokines. Recently, it has been shown that bacteria have an influential role in the immunomodulation of host mediators and hence host immune response. Indeed, dysregulation of the host immune response, as well as a dysbiosis of the oral microbial community, has been attributed to the pathogenesis of periodontal disease. However, the few investigations into the interaction between the subgingival microbial community and the host immune response have provided limited information to understand this relationship. Therefore, a full assessment of the host-bacterial interaction in health and disease is necessary to further our understandings of the etiology of periodontal disease and identify novel biomarkers of this disease. This thesis investigates the interaction of subgingival microbiome and the host immune response for both health and disease with disease defined as induced gingivitis. A comprehensive evaluation of forty major chemokines and inflammatory mediators in the gingival crevicular fluid (GCF) was achieved by multiplex immunoassay. In parallel, 16S rRNA next-generation sequencing was performed to characterize microbial community composition and structure. Lastly, neutrophil infiltration was assessed by myeloperoxidase (MPO) detection in the GCF to correlate neutrophil recruitment with chemokine expression patterns. The cross-sectional study in healthy adolescents showed inter-individual variability in the chemokine expression patterns and the subgingival microbial profile. Two different chemokine expression patterns were observed among study participants; however, the different groups did not share common microbiome profiles. Additionally, there was no significant concordance between the combined chemokines and microbial profiles in gingival health. Altogether, this data provides a better understanding of the interaction between the immune response and microbiome in the state of clinical health. Findings from the experimental gingivitis study demonstrated that during the initial transition from clinical health to gingivitis, there was a significant shift in the microbial composition that paralleled an alteration in host homeostasis. Despite variable immune responses to plaque accumulation, this alteration was characterized by a decrease in neutrophil chemotactic factors within most patients. Furthermore, patients were able to be separated into three distinct categories with unique microbial and chemokine profiles based on their immune response. The result of this work highlights the influential effect of host response and microbiome in the susceptibility to periodontal disease. In conclusion, this study contributes to our understanding of the host-bacterial interaction in health and the changes which occur during gingivitis induction. The significant alteration of multiple chemotactic factors within the GCF also provides the potential for a novel gingivitis diagnostic tool.
Thesis (Ph.D.)--University of Washington, 2019
Keywords: Chemokine; Gingival crevicular fluid; Gingivitis; Microbiome; Neutrophil; Plaque; Dentistry; Microbiology; Immunology; Dentistry